Near-to-planar 3-jet events in and beyond QCD perturbation theory - Banfi, A; Dokshitzer, Y; Marchesini, G; Zanderighi, G (2001)
We present the results of QCD analysis of out-of-event-plane momentum distribution in 3-jet e+e- annihilation events. We consider the all-order resummed perturbative prediction and the leading power suppressed non-perturbative corrections to the mean value 〈Kout〉 and the distribution and explain their non-trivial colour structure. The technique we develop aims at improving the accuracy of the theoretical description of multi-jet ensembles, in particular in hadron-hadron collisions. © 2001 Published by Elsevier Science B.V.